Proposition of Cutoff Points for Anthropometric Indicators to Identify High Blood Pressure in Adolescents - Borges, Leandro Lima; Gerage, Aline Mendes; Monteiro, Luciana Zaranza; Ulbrich, Anderson Zampier; Silva, Diego Augusto Santos (Frontiers in Nutrition, 2022)
Aim: To propose cutoff points for anthropometric indicators for high blood pressure (HBP) screening in adolescents and to identify, among these indicators, those more accurate for boys and girls. Methods: This cross-sectional study was carried out in the city of São José, SC, Brazil with 634 adolescents aged 14-19 years. Blood pressure levels were measured using a digital oscillometric sphygmomanometer and adolescents were classified as having HBP or not. Anthropometric indicators were calculated based on anthropometric measurements such as: body mass (BM), height, waist circumference (WC), hip circumference (HC) and triceps, subscapularis, suprailiac and mid-calf skinfold thickness (SF). The Receiver Operating Characteristic Curve (ROC) was used to analyze the predictive capacity of anthropometric indicators in the identification of HBP. Results: Higher values of Area Under the Curve (AUC) were for the anthropometric indicators BM (0.67; 95%CI: 0.62-0.72), body mass index (BMI) (0.67; 95%CI: 0.62-0.72) and WC (0.67; 95CI%: 0.62-0.71) for males. For females, no anthropometric indicator had discriminatory power for HBP screening. The cutoff points for the anthropometric indicators with discriminatory power for HBP screening in males were BM > 64.80 Kg, BMI > 21.76 Kg/m², fat percentage (FP) > 15.75, waist height to ratio (WHtR) > 0.41, WC > 73.00 cm and HC > 92.25 cm. Conclusion: Anthropometric indicators of body adiposity had greater discriminatory power of HBP screening in males. For females, caution is suggested because the anthropometric indicators showed AUC values (95%CI) below 0.60.